Mangrove afforestation increases microbial necromass but reduces their contribution to soil carbon pool - Huihuang Liao; Youshao Wang; Yanwu Zhou; Zhimao Mai; Hui Wang; Weiwen Zhou; Dongxi Liu; Hao Cheng (Ecological Indicators)
Despite the widely acknowledged importance of microbial necromass carbon (MnC) in carbon sequestration, the mechanisms regulating MnC accumulation in mangroves remain poorly understood. Therefore, a mangrove rehabilitation demonstration zone, comprising native Kandelia obovata, exotic Sonneratia apetala, and unvegetated mudflat, was employed to investigate the variations in MnC after mangrove afforestation, as well as the underlying roles played by microorganisms and minerals. The results showed an obvious increase in MnC after mangrove afforestation. Compared with unvegetated mudflat, MnC increased from 0.81 g/kg to 1.09 g/kg and 3.05 g/kg in S. apetala and K. obovata soils, respectively. Mangrove afforestation, especially the plantation of K. obovata, also boosted bacterial and fungal quantities, leading to an increase in living microbial biomass carbon and MnC. The accumulation of MnC was also found to be positively correlated with amorphous iron oxides. Moreover, the findings from random forest and partial least squares path modeling analyses further suggested that mineral protection had a more significant contribution to MnC accumulation than microbial production. In addition, an interesting linkage was observed between mangrove afforestation and increased the K-strategy taxa both in bacteria and fungi, which diminished the contribution of MnC to soil carbon pool. In conclusion, this is the first attempt to reveal the mechanisms involved in MnC accumulation from the perspective of microbial production and mineral protection in mangroves. This study offers novel understandings of the mechanisms of carbon sequestration in mangroves.